Yvh1 protein phosphatase is required for pre-autophagosomal structure formation after TORC1 inactivation. Issue 12 (2nd December 2015) - Yeasmin, Akter M S T; Waliullah, Talukdar Muhammad; Kondo, Akihiro; Ushimaru, Takashi
Abstract: The pre-autophagosomal structure (PAS) is a putative site for autophagosome formation in budding yeast. Upon nutrient depletion or rapamycin treatment, target of rapamycin complex 1 (TORC1) becomes inactive, inducing PAS formation and autophagy. Here, we show that Yvh1 phosphatase is critical for PAS formation, but not autophagy induction, after TORC1 inactivation.